Intellectual Property Right of Transgenic Crops and Right to Work: Bioethical Challenges in Rural Communities - Heydari, Bahareh; Razmkhah, Najmeh (Bangladesh Journal of Bioethics, 2014)
Increasing importance of intellectual property rights (IPR) over the area of seed production, is radically transforming agricultural production relations. One major effect of this transformation is the exclusive control of biotech companies on process of transaction of GM crops. This new status, that is the part of a trend that was set in national and international documents to protect inventors, may have adverse impact on the right to work of poor and vulnerable farmers in developing countries. In the framework of international human rights, the right to work is the fundamental right of every one to have sustainable access to decent work that meets the needs and welfare of his livelihood. Rural communities enjoy this right similar to the urban communities. But, the main question, which is our major concern, is the relationship between IPR and the right to work with attention to articles of International Covenant on Economic, Social and Cultural right and International Treaty on Plant Genetic Resources for Food and Agriculture. DOI:http://dx.doi.org/10.3329/bioethics.v5i2.19619 Bangladesh Journal of Bioethics 2014 Vol.5 (2): 49-60.